2012
DOI: 10.1259/bjr/76693739
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 3 T MR diffusion tensor imaging for detection of the fibre architecture of the human uterus: a feasibility and quantitative study

Abstract: In vivo 3 T MR diffusion tensor imaging for detection of the fibre architecture of the human uterus: a feasibility and quantitative study Objective: The aim of this study was to investigate the feasibility of depicting fibre architecture of human uteri in vivo using 3 T MR diffusion tensor imaging (MR-DTI) with a three-dimensional (3D) tractography approach. Quantitative results were provided. Methods: In vivo 3 T MR-DTI was performed on 30 volunteers (9 Caesarean delivery). Main diffusion directions reflectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
2
33
1
Order By: Relevance
“…Current published studies include ex vivo and in vivo studies. [11][12][13][14][15][16] In 2006, threedimensional fibre architecture of the normal human uterus based on DTI has been ex vivo evaluated in five samples by Weiss et al 11 Toba et al 12 ex vivo study showed that DTI might be a useful tool for the diagnosis of myometrial invasion of uterine endometrial cancer. However, fractional anisotropy (FA) value of a normal uterus has not been thoroughly investigated yet.…”
Section: Yonglan He and Ning Ding Have Contributed Equally To This Armentioning
confidence: 99%
See 1 more Smart Citation
“…Current published studies include ex vivo and in vivo studies. [11][12][13][14][15][16] In 2006, threedimensional fibre architecture of the normal human uterus based on DTI has been ex vivo evaluated in five samples by Weiss et al 11 Toba et al 12 ex vivo study showed that DTI might be a useful tool for the diagnosis of myometrial invasion of uterine endometrial cancer. However, fractional anisotropy (FA) value of a normal uterus has not been thoroughly investigated yet.…”
Section: Yonglan He and Ning Ding Have Contributed Equally To This Armentioning
confidence: 99%
“…It would be ambiguous to use this MR parameter to evaluate malignancy situations without knowing the possible differences in various uterine structures, including endometrium, myometrium and junctional zone. In 2012, Fiocchi et al 13 investigated the feasibility of depicting fibre architecture of the human uterus in vivo using 3-T MR-DTI based on 30 volunteers in different menstrual phases (MPs). In 2013, Fujimoto et al 14 compared the DTI parameters in the different uterine layers of nine subjects in vivo, but limited their study group to the luteal phase (LP) only.…”
Section: Yonglan He and Ning Ding Have Contributed Equally To This Armentioning
confidence: 99%
“…Fiocchi et al (10) showed that the FA and ADC values of the whole uterus in a cesarean-scarred uteri group were 0.42±0.02 and 1.82±0. 18 these two groups, which were smaller in the cesarean section group.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging is the best method to evaluate the anisotropic properties of solid organs, and it, unlike DWI, permits the analysis of diffusion along multiple directions. Recently, the improvement of this technique made it a useful and complementary sequence to conventional imaging techniques for demonstrating the fiber structures of the uterus (4,8,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…With the improvement of the MRI hardware and softwares, fast imaging techniques, after the use of DWI also DTI was implemented to abdominal imaging for some of the abdominal organs like uterus. The initial researches have been published regarding DTI of the uterus specimens of the patients to whom hysterectomy was performed for medical reasons [24] and then in vivo on the uterus of the patients' [5] . Nonfunctional (conventional) MRI provides excellent anatomical information of the uterus, however, the morphological appearance still may not differentiate some of the benign and malignant uterine lesions [6] .…”
Section: Introductionmentioning
confidence: 99%